Evaluation of Analgesic Activity of Casuarina equisetifolia Frost (Casuarinaceae) - Aher, A.N.; Pal, S.C.; Yadav, S.K.; Patil, U.K.; Bhattacharya, S. (Asian Journal of Chemistry, 2010)
The formalin induced paw licking time in the early and late phases of mice were used to assess analgesic activity of methanolic extracts of wood, fruit, leaf and bark of Casuarina equisetifolia. The extracts of wood, leaf, fruit and bark have shown potent activity (3.40 ± 0.45, 4.60 ± 0.45, 6.40 ± 1.45 and 8.00 ± 1.45 phase II at the dose of 100 mg/kg). The wood extract (50 and 100 mg/kg) significantly attenuated the writhing responses induced by an intraperitoneal injection of acetic acid and delayed the time of reaction of mice to thermal stimulation produced by the hot plate. The profound activity of wood may be contributed by high quantity of tannic acid (22.97 % w/w), estimated by Folin-Ciocalteu reagent. The results confirmed central and peripheral analgesic activities of wood extract and affirm the claim by Fijian traditional medicine practitioners.